Assessment of diaphragmatic thickness as a predictor for intubation in pneumonia patients - Elzahraa Wagdy Abdelfatah; Salwa Hussein Abdelmoneim; Hend Yahia Zakaria; Fatmaalzahraa Saad Abdalrazik (Monaldi Archives for Chest Disease)
Pneumonia, one of the major contributors to morbidity and mortality globally, often leads to serious complications such as respiratory failure. Diaphragmatic dysfunction, detected through ultrasound, may predict the need for intubation in patients with pneumonia. This study aimed to evaluate the roles of diaphragmatic thickness fraction (DTF) and diaphragmatic excursion (DE) as predictors of intubation in pneumonia patients. This follow-up cohort study involved 53 participants diagnosed with pneumonia. Diaphragmatic ultrasonography was performed to measure DTF and DE within 24 hours of admission. The mean age of the patients was 51.8±20.4 years, with 66% being male. Diabetes mellitus (DM) (p=0.000) and hypertension (HTN) (p=0.003) were significantly associated with the need for intubation. DE was significantly correlated with intubation (p=0.001). At a cut-off of 2.9 cm, DE demonstrated 100% sensitivity and 56% specificity for predicting intubation. DTF exhibited 92% sensitivity and 60% specificity at a cut-off of 0.52, with a positive predictive value of 85% and a negative predictive value of 54%. Diaphragmatic parameters, particularly DE and DTF, are significant predictors of intubation in pneumonia patients. Comorbidities such as DM and HTN also play a critical role, underscoring the importance of early identification of high-risk patients for timely intervention.